Variability, Heritability and Genetic Advance for Growth Parameters in Populus deltoides - Verma, R. C.; Bangarwa, K.S. (Indian Forester, 2007)
The variability, heritability and genetic advance was studied in 60 clones of Populus deltoides under nursery conditions during 2000 and 2001. The data was recorded for sprouting percentage, survival percentage, total height, basal diameter, clear bole height, number of branches, tapering and internodal length and analysed. The Phenotypic Coefficient of Variation, Genotypic Coefficient of Variation & Heritability estimates reflected the predominance of heritable variation for total height, basal diameter, clear bole height and number of branches. The estimates of genetic advance as percentage of mean suggested the potentiality of clonal material for improvement through selection for total height, basal diameter, clear bole height and number of branches.